2019
DOI: 10.1007/s40675-019-00142-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Stroke: New Updates on Epidemiology, Pathophysiology, Assessment, and Treatment

Abstract: Purpose of review-This review aims to discuss the most recent data on sleep disorders and stroke, highlighting relevant findings for the practicing neurologist or health providers who encounter patients with sleep disorders and stroke. Recent findings-Sleep apnea and abnormal sleep duration have the strongest association with stroke risk. Possible mechanisms include non-dipping of blood pressure during sleep, hypoxemia or reoxygenation leading to sympathetic activation, hypertension, atrial fibrillation and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 132 publications
0
9
0
Order By: Relevance
“…Stroke incidence in OSA-positive patients Results from three cohort studies reported by Dae Lim Koo (2018) [3] H. Lee Lau et al (2019) estimate a relative risk of independent association between SAS and stroke of 2.5 in a meta-analysis of 10 cohort studies [4] Sherma (2016) analysing the Sleep Heart Health Study and Wisconsin studies gives the respective results: HZ =2.86 and RR = 4.48 (ci: 1.31 -15.33) [5] Prevalence of OSA in stroke/TIA The results of a meta-analysis and systematic review of 89 studies involving 7,096 patients by Andreas Seiler (2019) are as follows: for AHI >5 events/hour, the prevalence is 71% of patients, for AHI>30 events/hour, the prevalence is 30% of patients [6]. The observational polysomnographic study by Sebastian R. Ott (2020) gives a prevalence of 80.5% for an AHI > 5 events/hour and 25.4% for an AHI > 30 events/hour [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…Stroke incidence in OSA-positive patients Results from three cohort studies reported by Dae Lim Koo (2018) [3] H. Lee Lau et al (2019) estimate a relative risk of independent association between SAS and stroke of 2.5 in a meta-analysis of 10 cohort studies [4] Sherma (2016) analysing the Sleep Heart Health Study and Wisconsin studies gives the respective results: HZ =2.86 and RR = 4.48 (ci: 1.31 -15.33) [5] Prevalence of OSA in stroke/TIA The results of a meta-analysis and systematic review of 89 studies involving 7,096 patients by Andreas Seiler (2019) are as follows: for AHI >5 events/hour, the prevalence is 71% of patients, for AHI>30 events/hour, the prevalence is 30% of patients [6]. The observational polysomnographic study by Sebastian R. Ott (2020) gives a prevalence of 80.5% for an AHI > 5 events/hour and 25.4% for an AHI > 30 events/hour [7].…”
Section: Epidemiologymentioning
confidence: 99%
“…Sleep is an essential component of daily functioning and is progressively acknowledged as a factor influencing long-term well-being [ 1 ]. Sleep can be affected by several conditions, and this can concur with cerebrovascular risk [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Dysphagia and airway collapse can lead to increased airway resistance, which is a common manifestation after stroke and is directly associated with SAs. [ 11 ] Airway obstruction can also occur if the stroke causes severe physical disability, prolonged bed rest, fluid retention in the neck, and increased tissue pressure. [ 12 ] Same limb movement leads to the limitation of sleep posture and the increase of supine posture, which becomes one of the reasons for the increased AHI.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Same limb movement leads to the limitation of sleep posture and the increase of supine posture, which becomes one of the reasons for the increased AHI. [ 11 ] Moreover, the pathological changes in substance metabolism and vascular endothelium associated with SAs also increase the risk of stroke. [ 13 ] It is possible that these factors accelerate the formation of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%